ABOUT THE ROMANIAN SOCIETY FOR ENGINEERING GRAPHICS - SIMION Ionel (Journal of Industrial Design and Engineering Graphics, 2015)
SORGING is a non-profit, non-governmental society, opened to all professionals interested in Engineering Graphics and Design. It aims to promote the research, development and innovation activities, together with the dissemination of best practices and assistance for educational purposes. In this paper the research and educational activities of the Romanian Society for Engineering Graphics will be briefly reviewed.